TINDAKAN SEKSIO SESARIA DAN KEJADIAN TRANSIENT TACHYPNEA OF THE NEWBORN (TTN) - Dwijayanti, Juwita; Sumarah, Sumarah; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2014)
Business of the millennium development goals (MDGs) one of them is to reducing infant mortality rate ( AKB ) to 23 per 1,000 of live births in the year 2015. The babies in Indonesia hopely can birth safe and healthy, living one through childbirth operation seksio sesaria. Seksio sesaria is one factor cause of the accident transient tachypnea of the newborn (TTN). The purpose to know the relation of the act of seksio sesaria against the incident transient tachypnea of the newborn (TTN) in rsud wates 2013. A method of observational analytic, research design kohort prospective. The location of research in rsud wates. The sample with purposive of sampling. Respondent a new baby born with the act of seksio sesaria and born spontaneous. Time research the 29th juli-16 august 2013. The number of subjects according to criteria as many as 40 the subjects. Divided into two groups, namely the group exposure to (birth with sectio secarea) and a group not exposed to (birth with normaly) each as much as 20 the subjects. Test hypotheses using chi-square. A kind of scale nominal. Result: there are relations between the act of sectioio secarea against the incident transient tachypnea of the newborn (TTN) with p-value 0,00, and coefficients contingency 0,646 category level is strong, and known the act of seksio sesaria risky 3,2 times to the occurrence of TTN compared with the birth of spontaneous. Conclusions: there is a relationship the act of seksio sesaria against the incident transient tachypnea of the newborn (TTN) and birth in sectio secarea risky 3,2 times to the occurrence of TTN.